2014
DOI: 10.1093/neuonc/nou303
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical antitumor efficacy of selective exportin 1 inhibitors in glioblastoma

Abstract: SINE compounds show preclinical efficacy utilizing in vitro and in vivo models of GBM, with induction of apoptosis as the mechanism of action. Selinexor is now in early clinical trials in solid and hematological malignancies. Based on these preclinical data and excellent brain penetration, we have initiated clinical trials of Selinexor in patients with relapsed GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 29 publications
1
67
1
Order By: Relevance
“…8 In addition, selinexor has demonstrated excellent brain penetration and promising results in both pre-clinical and clinical models of glioblastoma. 9,10 Recently, a phase 2 study in patients with recurrent glioblastoma showed 17% of PR and 33% of stable disease in 12 patients, which confirms its activity in brain tumors. 9 Finally, our group studied the effect of selinexor in a pre-clinical model of PCNSL using an intracerebral xenograft murine model.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…8 In addition, selinexor has demonstrated excellent brain penetration and promising results in both pre-clinical and clinical models of glioblastoma. 9,10 Recently, a phase 2 study in patients with recurrent glioblastoma showed 17% of PR and 33% of stable disease in 12 patients, which confirms its activity in brain tumors. 9 Finally, our group studied the effect of selinexor in a pre-clinical model of PCNSL using an intracerebral xenograft murine model.…”
mentioning
confidence: 86%
“…7,8 Moreover, selinexor has shown excellent brain penetration and encouraging efficacy in patients with recurrent glioblastoma. 9,10 Promising results in pre-clinical models of primary CNS lymphoma (PCNSL) have been reported as well. 11 The efficacy of selinexor in patients with SCNSL or PCNSL has not yet been demonstrated.…”
mentioning
confidence: 99%
“…These data were indicative of synergistic regulatory effects between the two lncRNAs. Within this module, XPO1 was associated with GBM prognosis [38]. To evaluate the association between the 5-ceRNA module and GBM survival, we integrated the expression profiles of the nodes into a risk model (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…MCM3AP-AS, which is involved in RNA processing and cell cycle-related functions, was significantly associated with survival. By exploring the highly competitive sub-network of the LMCN, we determined that MCM3AP-AS and MIR17HG comprised a ceRNA regulating module that competed with MATR3, ZCCHC14, and XPO1, which was associated with GBM prognosis [38]. By integrating the expression profile of this module into a risk model, we could stratify GBM patients from both the TCGA and the GSE7696 datasets into different risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Different from research exploring the mechanism of tumor transplantation and blood metastases as the object of study, this study primarily compared the efficacy of EGFR-TKIs in the treatment of intracranial tumors, for which the direct intracranial transplant method created a more consistent model. Furthermore, whether in drug efficacy studies of metastatic brain tumors or intracranial primary tumors, this type of animal model is widely applied [20, 42, 43]. Secondly, in this study, we did not investigate the potential effect of WBRT on the penetration of EGFR-TKIs into the CSF.…”
Section: Discussionmentioning
confidence: 99%